Ameliorative effect of zinc and manganese supplementation in buffalo calves during hot climatic conditions - SINGH, GYANENDRA; HOODA, O K; MAHAPATRA, R K; MEUR, S K; VARSHNEY, V P (The Indian Journal of Animal Sciences, 2011)
Ameliorative effect of zinc and manganese on buffaloes was studied during natural hot summer climate. Buffalo calves (18) of either sex in age group of 6â€“7 months were divided in groups A, B and C of 6 each. Group A was supplemented with zinc sulphate @500 mg/ animal/ day, group B was supplemented with zinc sulphate @500 mg/ animal/ day plus MnCl2 @500 mg/ animal/day daily during the experimental period, while group C was kept as control. Respiration rate, pulse rate and rectal temperature increased significantly from morning to evening, while animals of zinc sulphate supplemented group had significantly lower respiration rate in the evening compared to other groups. The activity of alkaline phosphatase and concentration of glucose, cholesterol, triglyceride, calcium, magnesium, potassium, triiodothyronine (T3) and thyroxine (T4) did not vary significantly different among groups. However, in zinc sulphate supplemented group, the concentration of blood urea and aspartate aminotransferase decreased significantly compared to control and zinc sulphate plus manganese chloride supplemented group. The significantly higher plasma sodium concentration was observed in zinc sulphate and zinc sulphate plus manganese chloride supplemented group compared to control group. Our results indicated that supplementation of zinc sulphate during hot summer may ameliorate some effect of heat stress in buffalo calves.Â